Magnetic Spin Susceptibility of quasi-particles in metals using the Landau Fermi Liquid Theory - Adesakin G. E., Edema O. G., Adekoya M. A. & (Covenant Journal of Physical and Life Sciences, 2020)
38 In this work, the magnetic spin susceptibility of quasi-particles in metals were computed for some metals based on the modified Landau Fermi Liquids Theory using the electron density parameter. The results showed that for each metal, the Landau magnetic spin susceptibility of quasi-particles is higher than the computed magnetic spin susceptibility of quasi-particles and experimental values. This may be due to the fact that the Landau parameter must have been over estimated in its application. The computed magnetic spin susceptibility of quasi-particles is in good agreement with the experimental values of metals available with a remarkable agreement at. The better estimation of the magnetic spin susceptibility of quasi-particles using the modified Landau Fermi Liquid theory were compared with available experimental values. This show that the introduction of the electron density parameter in the Landau Fermi Liquid theory is promising in predicting the contribution of quasi-particles to the bulk properties of metals. The magnetic spin susceptibility of quasi-particles for transition metals is higher than most of the magnetic spin susceptibility of quasi-particles for alkali metals. This suggests that the magnetic spin susceptibility is considerably higher for most transition metals due to the incomplete inner electronic shells as more quasi-particles can be excited which enhances their susceptibility than the alkali metals.